Basalt fiber reinforced composite material and preparation method thereof

Through the preparation method of modified resin matrix and basalt fibers, the problem of brittle fracture of fiber-reinforced composite materials under impact or wear conditions is solved, and the efficient preparation of composite materials and excellent mechanical properties are achieved, which is suitable for a wide range of application fields.

CN119431840APending Publication Date: 2025-02-14EAST CHINA JIAOTONG UNIVERSITY

Patent Information

Application Number
CN202411548093.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

High-strength fiber reinforced composites are prone to brittle fracture or damage under impact or wear conditions, and cannot achieve the expected fiber reinforcement effect.

Method used

The toughening agent is prepared by mixing the nanosilica powder with polyethylene glycol and mixed with the resin matrix, surfactant and curing agent to improve the dispersion efficiency. At the same time, the modified basalt fiber fabric is cut for hot pressing bonding on the bonded section, and then cured by heat treatment and curing. Finally, the modified resin matrix and modified basalt fibers are made into a composite material through a vacuum bag pressure diversion molding process.

Benefits of technology

Shorten the preparation time, improve the dispersion efficiency of toughener, ensure the reinforcement performance of modified basalt fibers, improve the impact resistance and ductility of composite materials, is suitable for commercial production, and meets the high-performance composite in different fields. Material requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431840A_ABST
    Figure CN119431840A_ABST
Patent Text Reader

Abstract

The invention provides a basalt fiber reinforced composite material and a preparation method thereof. The preparation method comprises the following steps: preparing a toughening agent; preparing a modified resin matrix; preparing the modified basalt fiber; and curing and molding the composite material. The preparation method provided by the invention can shorten the preparation time, improve the dispersion efficiency of the flexibilizer and improve the toughening effect, has good economic benefits, and is more suitable for commercial production. Besides, the basalt fiber reinforced composite material prepared by the method not only has the characteristics of corrosion resistance, high temperature resistance and environmental protection, but also has better impact resistance and ductility while enhancing the mechanical strength and the mechanical property of the composite material, so that the composite material disclosed by the invention has a wider application field and is worthy of popularization and application. The method is suitable for the fields of buildings, automobiles, war industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, in particular to the technical field of formed composite materials containing toughening materials, and specifically relates to a basalt fiber reinforced composite material and a preparation method thereof. Background Art

[0002] Basalt fiber is a high-performance, environmentally friendly fiber material with outstanding durability. It can be used to replace traditional composite materials with glass fiber as reinforcement. Basalt fiber composite panels have excellent properties such as light weight and high strength, green environmental protection, corrosion resistance and flame retardancy. They have broad application prospects and are widely used in important fields such as construction, automobiles and military industry.

[0003] High-strength fiber-reinforced composite materials usually have the characteristics of light weight, high strength, good chemical stability and corrosion resistance, and can be widely used in aviation, aerospace, military industry, medical equipment and other fields. However, high-strength fiber-reinforced composite materials are usually prone to brittle fracture or damage under certain impact or wear conditions, and cannot achieve the expected fiber reinforcement effect.

[0004] CN118599288A discloses a fiber-reinforced resin-based composite material based on a shear thickening fluid and a preparation method thereof. The composite material prepared by modifying different types of resins with a shear thickening fluid has better performance in static stretching, bending and low-speed impact.

[0005] CN118652498A discloses a basalt fiber reinforced polypropylene composite material, a preparation method and application thereof, and improves the strength and toughness of the polypropylene composite material by using a combined modifier including a water-soluble resin, a nano-metal oxide, a coupling agent, a plasticizer and a defoaming agent. Summary of the invention

[0006] The present invention provides a method for preparing a basalt fiber reinforced composite material, which can shorten the preparation time, improve the dispersion efficiency of the toughening agent, ensure the reinforcing performance of the modified basalt fiber, improve the toughening effect, have good economic benefits, and be more suitable for commercial production. The basalt fiber reinforced composite material prepared by the method of the present invention not only has the characteristics of corrosion resistance, high temperature resistance and environmental protection, but also has better impact resistance and ductility while enhancing the mechanical strength and mechanical properties of the composite material, so that the composite material of the present invention can meet the needs of high-performance composite materials in different fields, and has a wider range of application fields, such as construction, automobiles, and military industries.

[0007] In a first aspect, the present invention provides a method for preparing a basalt fiber reinforced composite material, characterized in that it comprises the following steps:

[0008] Preparation of toughening agent: mixing nano silicon dioxide powder with polyethylene glycol to obtain toughening agent;

[0009] Preparation of modified resin matrix: mixing the toughening agent with the resin matrix, the first surfactant and the curing agent to obtain the modified resin matrix, wherein the mixing includes mechanical stirring, ultrasonic treatment and low temperature heating technology;

[0010] Preparation of modified basalt fiber: providing cut basalt fiber cloth and bonding the cross sections, mixing the toughening agent with the second surfactant, impregnating the basalt fiber cloth, compacting the basalt fiber cloth, and curing by heat treatment to obtain modified basalt fiber;

[0011] Curing and molding of composite materials: The modified resin matrix and modified basalt fiber are made into composite materials through vacuum bag pressure infusion molding process.

[0012] Preferably, the first surfactant is selected from one or more of sodium dodecyl sulfate (SDS), quaternary ammonium salts, and polysorbate 80. More preferably, the first surfactant is sodium dodecyl sulfate (SDS).

[0013] Preferably, the bonding section includes thermal compression bonding, in which the sections of the basalt fiber cloth are heated and pressed together under certain temperature and pressure conditions, so that the sections are bonded through melting and solidification of the thermoplastic material.

[0014] Preferably, the compacting includes placing the basalt fiber cloth into a roller press and rolling a roller thereon to perform roller compaction on the basalt fiber cloth.

[0015] Preferably, the heat treatment curing comprises placing the impregnated basalt fiber in an oven at 120° C. for curing for more than 6 hours to obtain modified basalt fiber.

[0016] In one embodiment, the mass per unit area of ​​the modified basalt fiber is 350 g / m 2 The tensile strength in the warp direction is 3263N / 5cm, the tensile strength in the weft direction is 2208N / 5cm, and the elongation at break is 3%.

[0017] In a second aspect, the present invention provides a basalt fiber reinforced composite material prepared by the method of the first aspect.

[0018] In a third aspect, the present invention further provides the use of the basalt fiber reinforced composite material of the second aspect of the present invention in the fields of construction, automobiles and military industry. For example, the basalt fiber reinforced composite material of the present invention is used in bridge bottom plates, automobile body parts and bulletproof structures.

[0019] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention, as well as the technical features specifically described below (such as embodiments), can be combined with each other to form new or preferred technical solutions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A schematic diagram of the vacuum bagging infusion molding process used in the present invention is shown.

[0021] Figure 2 The diagram shows the operation of the vacuum bagging induction molding process used in the present invention.

[0022] Figure 3 The peak load (peak force) test results under different energy impacts in the dynamic mechanical property test of the embodiments of the present invention and the comparative examples are shown.

[0023] Figure 4 The peak displacement test results of the embodiments of the present invention and the comparative examples under different energy impacts in the dynamic mechanical property test are shown.

[0024] Figure 5 The Hopkinson pressure bar test results of the modified resin matrix prepared by the method of the present invention are shown.

[0025] Figure 6 A schematic diagram of the apparatus for the Hopkinson pressure bar experiment is shown.

[0026] Figure 7 The experimental results of modified resin matrix with different toughening agent dosages under 0.4 MPa impact pressure are shown. DETAILED DESCRIPTION

[0027] The present invention will be further described in detail below. Such description is for illustrative purposes only and is not intended to limit the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. Those skilled in the art can make various modifications and changes without departing from the spirit of the present invention.

[0028] General Definitions and Terminology

[0029] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In the event of a conflict, the definitions provided herein shall prevail.

[0031] Unless otherwise indicated, all percentages, parts, ratios, etc. are by weight.

[0032] When quantity, concentration or other value or parameter is given as range, preferred range or preferred upper limit and lower limit or specific value, it should be understood as specifically disclosing all ranges formed by paired values ​​from any upper limit range or preferred value and any lower limit range or preferred value, regardless of whether the range is disclosed individually. Unless otherwise stated, when numerical range is quoted herein, described range refers to including its endpoints and integers and fractions within all such ranges. The scope of the present invention is not limited to the specific numerical value quoted when defining the range. For example, "12-200" encompasses 12, 20, 40, 50, 60, 80, 100, 120, 140, 160, 180 or 200, and any sub-range consisting of any two values ​​therein, such as 12-180, 20-160, 50-140, 60-120, etc.

[0033] The terms "about" and "approximately" when used in conjunction with a numerical variable generally refer to the value of that variable and all values ​​of that variable are within the experimental error (e.g., within a 95% confidence interval for the mean) or within ±10% of the specified value, or within a wider range (e.g., within ±15%, within ±20%, within ±25%, or within ±30%).

[0034] The terms "comprises", "includes", "has", "contains" or "involves" and other variations thereof herein are inclusive or open-ended and do not exclude other unlisted elements or method steps. It will be understood by those skilled in the art that the above terms such as "comprising" encompass the meaning of "consisting of". The expression "consisting of" excludes any element, step or ingredient not specified. The expression "consisting essentially of" means that the scope is limited to the specified elements, steps or ingredients, plus the optional presence of elements, steps or ingredients that do not substantially affect the basic and novel features of the claimed subject matter. It will be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".

[0035] The terms "one or more" or "at least one" as used herein refer to one, two, three, four, five, six, seven, eight, nine or more.

[0036] When describing methods, components or steps, letters or numbers are used for the purpose of distinction only, and do not limit these methods, components or steps to be performed in the order or sequence of the identification. Those skilled in the art can make reasonable adjustments. For example, "first surfactant" and "second surfactant" are only used for the purpose of distinction, and do not indicate that there is a sequence or order relationship between the two. The objects referred to by different identifications can be the same or different.

[0037] In addition, if the number of parts or components of the present invention is not indicated before, it means that there is no limit to the number of occurrences (or existence) of the parts or components. Therefore, it should be interpreted as including one or at least one, and the singular form of the parts or components also includes the plural form, unless the numerical value obviously represents the singular.

[0038] Preparation method of the present invention

[0039] The present invention provides a method for preparing a basalt fiber reinforced composite material, characterized in that it comprises the following steps:

[0040] Preparation of toughening agent: mixing nano silicon dioxide powder with polyethylene glycol to obtain toughening agent;

[0041] Preparation of modified resin matrix: mixing the toughening agent with the resin matrix, the first surfactant and the curing agent to obtain the modified resin matrix, wherein the mixing includes mechanical stirring, ultrasonic treatment and low temperature heating technology;

[0042] Preparation of modified basalt fiber: providing cut basalt fiber cloth and bonding the cross sections, mixing the toughening agent with the second surfactant, impregnating the basalt fiber cloth, compacting the basalt fiber cloth, and curing by heat treatment to obtain modified basalt fiber;

[0043] Curing and molding of composite materials: the modified resin matrix and the modified basalt fiber are made into composite materials through vacuum bag pressure infusion molding process.

[0044] Preparation of toughening agent

[0045] The preparation method of the invention comprises: mixing nano silicon dioxide powder with polyethylene glycol to obtain a toughening agent.

[0046] In one embodiment, the form of the nano silicon dioxide powder of the present invention is one or more of spherical, rod-shaped, fibrous and porous, preferably spherical. In another embodiment, the particle size range of the nano silicon dioxide powder of the present invention is about 10-240nm, preferably about 10-200nm, more preferably 50nm. In a specific embodiment, the nano silicon dioxide used in the present invention is a spherical nano silicon dioxide with a particle size of about 50nm.

[0047] In one embodiment, the polyethylene glycol of the present invention is selected from one or more of polyethylene glycol 200, polyethylene glycol 400 and polyethylene glycol 600, preferably polyethylene glycol 200.

[0048] In one embodiment, silicon dioxide powder and polyethylene glycol are mixed at a mass ratio of 1:19 to obtain a toughening agent. In a specific embodiment, spherical nano-silicon dioxide with a particle size of about 50 nm is mixed with polyethylene glycol 200 to obtain a toughening agent. In another specific embodiment, the weight of silicon dioxide in the toughening agent prepared by the present invention accounts for about 5% of the total weight of the toughening agent, and a toughening agent with a concentration of 5% is obtained.

[0049] By selecting the morphology and particle size of nano-silica powder and the type of polyethylene glycol, the toughening agent prepared therefrom can have various excellent properties such as suitable fluidity, dispersibility and ductility, which is conducive to the interaction between the toughening agent and the resin matrix and basalt fiber.

[0050] In the present invention, there is no particular limitation on the mixing method of nano-silica and polyethylene glycol, and those skilled in the art can make conventional selections according to specific needs. For example, nano-silica and polyethylene glycol are physically mixed, including but not limited to mixing by methods such as ball milling, high pressure, swelling and extrusion. For example, the mixing of nano-silica and polyethylene glycol of the present invention can be carried out by mechanical stirring, ultrasonic treatment and low-temperature heating. In one embodiment, ultrasonic waves with a frequency of 40kHz are selected for treatment. In another embodiment, low-temperature heating is performed using a water bath temperature of 80°C. In yet another embodiment, the speed range of the agitator used for mechanical stirring is about 100r / min-2000r / min, which gradually increases according to the continuous increase in solution concentration.

[0051] In one embodiment, the preparation of the toughening agent also includes vacuum degassing. Vacuum degassing is a process that uses a vacuum environment to remove bubbles from liquids or soft materials. In a vacuum environment, the gas expands and is released from the liquid or soft material, thereby achieving the purpose of degassing. This process can effectively remove air and dissolved gases mixed into the material, and improve the uniformity and consistency of the material. In the present invention, the vacuum degassing includes placing the material to be treated in a 60°C vacuum drying oven and drying it for 24 hours. In one embodiment, the mixed nano-silicon dioxide powder and polyethylene glycol are placed in a 60°C vacuum drying oven and dried for 24 hours for vacuum degassing. Through this step, excess water can be removed, and bubbles introduced during stirring and ultrasound can be removed at the same time.

[0052] In the present invention, nano-silicon dioxide powder is mixed with polyethylene glycol, and the resulting toughening agent can also be called shear thickening fluid (STF). As a non-Newtonian fluid with shear thickening phenomenon, STF will harden rapidly when subjected to a large external impact. This unique shear thickening phenomenon enables STF to have excellent energy absorption and impact resistance. STF is widely used in the field of impact protection due to its unique stress responsiveness.

[0053] The toughening agent has excellent energy absorption, shock absorption and toughening effects, and can provide significant advantages in improving impact resistance and ductility. In particular, composite materials with a higher content of toughening agent have better energy absorption, shock absorption and toughening effects. In one embodiment, the mass ratio of the toughening agent to the resin matrix is ​​not less than 1:19, for example, not less than 1:9, 3:17, 1:4 or 1:3.

[0054] Preparation of modified resin matrix

[0055] The preparation method of the invention comprises: mixing a toughening agent with a resin matrix, a first surfactant and a curing agent to obtain a modified resin matrix.

[0056] In one embodiment, the resin matrix of the present invention is selected from epoxy acrylic resin, polyester resin or unsaturated polyester resin, preferably epoxy acrylic resin, for example. In another embodiment, the first surfactant of the present invention is selected from one or more of sodium dodecyl sulfate (SDS), quaternary ammonium salts, and polysorbate 80. In a preferred embodiment, the first surfactant is sodium dodecyl sulfate (SDS).

[0057] The traditional method of dispersing toughening agents into resin matrix is ​​mainly mechanical stirring. However, mechanical stirring can only disperse nano silicon dioxide powder into the resin matrix to a certain extent, and cannot make it dispersed completely, and it takes a long time. In order to obtain a better dispersion effect and improve efficiency, the present invention adds a first surfactant, and further adds ultrasonic treatment and low-temperature heating technology treatment on the basis of mechanical stirring, so that the dispersion rate of nano silicon dioxide powder in the resin matrix is ​​increased by more than 50%, and the preparation time can also be shortened by more than 50%, thereby improving the performance and preparation efficiency of the modified resin matrix, having good economic benefits, and being more suitable for commercial production.

[0058] In one embodiment, the preparation of the modified resin matrix includes mechanically stirring, ultrasonically treating and low-temperature heating a toughening agent with a concentration of 5% and an unsaturated polyester resin, adding a first surfactant, sodium dodecyl sulfate, and adding a curing agent of 1% based on the total mass of the toughening agent, the unsaturated polyester resin and the first surfactant to obtain a modified resin matrix. The present invention has no particular limitation on the curing agent of this step, and those skilled in the art can select a suitable curing agent as needed. For example, the curing agent of the present invention includes but is not limited to one or more of methyl ethyl ketone oxide, isopropylbenzene hydroperoxide and dodecyl peroxide, preferably methyl ethyl ketone oxide.

[0059] In one embodiment, the preparation of the modified resin matrix further includes vacuum degassing treatment. In one embodiment, the cured resin matrix is ​​placed in a vacuum drying oven at 60° C. and dried for 24 hours for vacuum degassing treatment.

[0060] Preparation of modified basalt fiber

[0061] The preparation method of the present invention comprises: providing cut basalt fiber cloth and bonding the cross sections, mixing a toughening agent with a second surfactant, impregnating the basalt fiber cloth, compacting the basalt fiber cloth, and curing by heat treatment to obtain modified basalt fiber.

[0062] Basalt fiber cloth is a continuous fiber material made of natural basalt as raw material and melted at high temperature. It is not only high in strength, but also has many excellent properties such as electrical insulation, corrosion resistance, and high temperature resistance. Its production process produces less waste and has little environmental pollution. After the product is discarded, it can be directly degraded in the environment without any harm and has environmental compatibility. The reserves of basalt ore on the earth are quite abundant, so the cost of basalt fiber is relatively low.

[0063] In the present invention, the bonding section includes heat-pressing bonding, in which the sections of the basalt fiber cloth are heated and pressed together under certain temperature and pressure conditions, so that the sections are bonded by melting and solidifying the thermoplastic material. In one embodiment, the thermoplastic material is selected from one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polycarbonate, polyamide, polyoxymethylene, and polymethyl methacrylate. In another embodiment, the thermoplastic material is polyethylene, more preferably strip-shaped polyethylene.

[0064] Those skilled in the art can select appropriate temperature and pressure of the bonding section according to the thermoplastic material used. For example, when the thermoplastic material is polyethylene, the temperature is 150° C. and the pressure is 5 MPa.

[0065] In one embodiment, the second surfactant is one or more of alkyl dimethyl betaine, sulfoethyl betaine, and phosphobetaine.

[0066] In one embodiment, the toughening agent and the basalt fiber are impregnated in a mass ratio of 1:1. The impregnation in the present invention includes covering the toughening agent on the entire surface of the basalt fiber cloth so that the toughening agent is in full contact with the basalt fiber cloth and is completely impregnated. In another embodiment, the toughening agent and the second surfactant are mixed and stirred to obtain a mixed solution, and the basalt fiber cloth is impregnated with the mixed solution, including covering the mixed solution on the entire surface of the basalt fiber cloth so that the mixed solution is in full contact with the basalt fiber cloth and is completely impregnated; wherein the mass ratio of the toughening agent contained in the mixed solution to the mass of the basalt fiber is 1:1.

[0067] There is no particular limitation on the compaction method of the basalt fiber cloth in the present invention, and those skilled in the art can select a suitable compaction method as needed. For example, the basalt fiber cloth is compacted by rolling. In one embodiment, compaction includes placing the basalt fiber cloth in a roller press and rolling a roller thereon to roll it. In one embodiment, the rolling speed of the roller is 1.5 m / min. In another embodiment, the size of the roller is 150×250 mm. In one embodiment, the pressure applied to the basalt fiber cloth by the roller press is 10 kN. Through the compaction step, the toughening agent can form a strong connection between the fibers, thereby improving the toughening effect.

[0068] The end point of impregnating and compacting the basalt fiber cloth is that the difference in mass between the basalt fiber cloth before and after impregnation does not exceed 1%.

[0069] In the present invention, the basalt fiber cloth is cured by heat treatment. The present invention has no particular restrictions on heat treatment, and those skilled in the art can select a suitable heat treatment method as needed. For example, the heat treatment can be performed by drying. In one embodiment, the heat treatment curing includes placing the impregnated basalt fiber in an oven at 120°C for curing for more than 6 hours to obtain modified basalt fiber. In another embodiment, the heat treatment curing is performed by a hot press, wherein the hot press is a 25T / 350XA hot press produced by Qingdao Huabo Machinery Technology Co., Ltd. The heat-treated basalt fiber cloth can have an enhanced bonding effect.

[0070] In one embodiment, the modified basalt fiber prepared by the method of the present invention has a mass per unit area of ​​350 g / m 2In another embodiment, the modified basalt fiber prepared by the method of the present invention has a tensile strength in the warp direction of 3263 N / 5 cm. In yet another embodiment, the modified basalt fiber prepared by the method of the present invention has a tensile strength in the weft direction of 2208 N / 5 cm. In one embodiment, the elongation at break of the modified basalt fiber prepared by the method of the present invention is 3%. By toughening and modifying the basalt fiber, the fracture toughness and impact resistance of the composite material containing the modified basalt fiber are improved.

[0071] Curing and molding of composite materials

[0072] The preparation method of the invention comprises: preparing a composite material from a modified resin matrix and modified basalt fibers by a vacuum bag pressure induction molding process.

[0073] The curing and molding of the composite material of the present invention is carried out by a vacuum bag pressure induction molding process. The vacuum bag pressure induction molding process is an efficient composite material manufacturing technology. By applying pressure by evacuating between the mold and the vacuum bag, the resin is impregnated with the reinforcing material and cured and molded, thereby obtaining a high-quality, high-performance composite material product. For example, the modified basalt fiber of the present invention is laid on the marble surface, and a demoulding cloth and a guide net are placed on the upper and lower sides thereof, respectively. A vacuum tube is placed at the end of the guide net. The modified basalt fiber, demoulding cloth, guide net and spiral guide tube are completely sealed and maintained in vacuum by a vacuum bag and a vacuum tube. The air in the vacuum bag film is extracted by a vacuum pump to make the modified basalt fiber fit closely to the mold surface. A mixed solution containing a toughening agent, an unsaturated polyester resin and a curing agent is introduced through a vacuum tube. The mixed solution flows along the guide net until the material in the sealed mold is completely soaked. After the curing is completed, the vacuum is released and separated by the demoulding cloth to obtain a composite material. In one embodiment, the concentration of the toughening agent used in the vacuum bag pressure induction molding process is 5%. In another embodiment, the mass ratio of the toughening agent to the unsaturated polyester resin used in the vacuum bagging infusion molding process is 1:19-3:7, preferably 3:37-11:29, for example, the mass ratio of the toughening agent to the unsaturated polyester resin is 1:19, 1:9, 3:17, 1:4 or 1:3, etc., preferably 1:9, 3:17, 1:4 or 1:3. The vacuum bagging infusion molding process uses a pressure control system to not only ensure the high density of the material, reduce voids and defects, and make the product have higher strength and durability, but also can produce products with complex shapes to meet various needs.

[0074] The preparation method of the basalt fiber reinforced composite material of the present application can make the toughening agent have excellent interaction with the resin matrix and the basalt fiber, shorten the toughening treatment time and improve the toughening effect.

[0075] The present invention also provides a basalt fiber reinforced composite material, which is prepared by the preparation method of the present invention.

[0076] The present invention further provides the use of the basalt fiber reinforced composite material prepared by the preparation method of the present invention in the fields of construction, automobile and military industry. For example, the basalt fiber reinforced composite material of the present invention is used for bridge bottom plates, automobile body parts and bulletproof structures.

[0077] Beneficial Effects

[0078] The present invention provides a method for preparing a basalt fiber reinforced composite material, which includes the modification of a resin matrix and basalt fibers. Among them, by specific operations such as bonding section treatment, impregnation and compaction of basalt fiber cloth, a modified basalt fiber suitable for a composite material with a stronger toughening effect is prepared, solving the technical problem that the section of basalt fiber cloth is easy to fall out and spread after cutting. By mechanical stirring, ultrasonic treatment and low-temperature heating technology treatment, the interaction between the toughening agent and the resin matrix and the basalt fiber is improved, the time required for preparation is shortened, and the method has good economic benefits and is suitable for commercial production.

[0079] The basalt fiber reinforced composite material prepared by the method of the present invention not only has the advantages of high strength, corrosion resistance, high temperature resistance and degradable environmental compatibility, but also has excellent mechanical strength and mechanical properties while having better impact resistance and ductility, so that the composite material of the present invention has a wider range of application fields, for example, it can be used to prepare bridge structure reinforcement plates, automobile bumpers, military equipment, etc.

[0080] Example

[0081] The solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0082] It should be noted that the following examples are merely examples for clearly illustrating the technical solutions of the present invention, and are not intended to limit the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description, and it is not necessary and impossible to exhaustively list all the embodiments here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention. Unless otherwise specified, the instruments, equipment, and reagents used herein are all commercially available.

[0083] Example 1 Preparation of basalt fiber reinforced composite material of the present invention

[0084] Step 1: Preparation of toughening agent

[0085] Spherical silicon dioxide powder with a particle size of 50 nm and polyethylene glycol 200 were selected as raw materials to prepare a toughening agent. Among them, the spherical silicon dioxide powder was provided by Zhenhan New Materials (Suzhou) Co., Ltd., and the polyethylene glycol 200 was provided by Wuhan Jixin Yibang Biotechnology Co., Ltd.

[0086] Under 40kHz ultrasonic conditions, the water bath temperature is adjusted to 80°C, and the silicon dioxide powder and polyethylene glycol 200 are stirred and mixed at a mass ratio of 1:19. The stirrer speed increases as the concentration of the solution increases, and the stirrer speed varies within a range of 100r / min-2000r / min. The treated solution is then placed in a 60°C vacuum drying oven and dried for 24 hours for vacuum degassing to obtain a toughening agent with a concentration of 5%. The concentration of the toughening agent is expressed as the mass fraction of silicon dioxide in the toughening agent.

[0087] Step 2: Preparation of modified resin matrix

[0088] Unsaturated polyester resin is selected as the resin matrix to prepare the modified resin matrix, wherein the unsaturated polyester resin model is 2504, provided by Tonglai Chemical Composite Materials Co., Ltd.

[0089] The 5% concentration toughener prepared in step 1 is stirred and mixed with the unsaturated polyester resin according to the mass ratio in Table 1 below, and the toughener is fully dispersed in the unsaturated polyester resin using an ultrasonic dispersion device, and the first surfactant sodium dodecyl sulfate and 1% of methyl ethyl ketone peroxide based on the total mass of the toughener, the unsaturated polyester resin and the first surfactant are added as a curing agent to obtain a mixed solution, and then the mixed solution is vacuum degassed to obtain a mixed solution of a modified resin matrix.

[0090] Table 1 Resin matrix dosage table of the embodiment of the present invention and the comparative example (mass percentage)

[0091]

[0092]

[0093] Step 3: Preparation of modified basalt fiber

[0094] Cutting basalt fiber cloth and bonding sections: Cut the basalt fiber cloth into the required specifications, and heat and press the sections of the basalt fiber cloth together at a temperature of 150°C and a pressure of 5Mpa through a hot press, so that the strips of polyethylene can be melted and solidified to achieve bonding. The hot press is produced by Qingdao Huabo Machinery Technology Co., Ltd., model 25T / 350XA.

[0095] Infiltrating basalt fiber cloth: Mix and stir the toughening agent prepared in step 1 at a concentration of 5% with the second surfactant alkyl dimethyl betaine to obtain a mixed solution, and use the mixed solution to infiltrate the basalt fiber cloth, wherein the mass ratio of the toughening agent prepared in step 1 at a concentration of 5% to the mass ratio of the basalt fiber is 1:1. Put the basalt fiber cloth into a roller press, and roll the roller slowly on it to roll it. The rolling speed of the roller is 1.5m / min, the pressure applied by the roller rotation is 10kN, and the size of the roller is 150×250mm. During the rolling process, ensure that the pressure of the roller is evenly distributed to avoid excessive or insufficient local pressure. Perform multiple rolling to improve the impregnation effect. After each rolling, check the impregnation effect of the fiber cloth, weigh the mass before and after impregnation, and ensure that the mass difference of each cloth after impregnation does not exceed 1%. Then arrange the impregnated basalt fiber in an oven at 120°C for curing for more than 6 hours to obtain modified basalt fiber.

[0096] Step 4: Curing of composite materials

[0097] Basalt fiber reinforced composites were prepared by vacuum bagging infusion molding process.

[0098] The modified basalt fiber prepared in step 3 is laid on the marble surface, and a demoulding cloth and a guide net are placed on the upper and lower sides thereof respectively, and a vacuum tube is placed at the end of the guide net. The modified basalt fiber, demoulding cloth, guide net and spiral guide tube are completely sealed and maintained in vacuum through a vacuum bag and a vacuum tube. A vacuum pump is used to extract the air in the vacuum bag film so that the modified basalt fiber fits tightly to the mold surface. The mixed liquid of the modified resin matrix prepared in step 2 is introduced through a vacuum tube, and the mixed liquid of the modified resin matrix prepared in step 2 flows along the guide net until the material in the sealed mold is completely soaked. After curing is completed, the vacuum is released, and the composite material is obtained by separation through the demoulding cloth.

[0099] Example 2 Dynamic mechanical properties test of the basalt fiber reinforced composite material of the present invention

[0100] The basalt fiber composite materials of embodiments 1-5 and comparative example 1 prepared in Example 1 were tested for relevant dynamic mechanical performance indicators under the same test conditions. The test was carried out according to the ASTM D7136 standard, and the test results are shown in Table 2 below, where the peak force indicates the magnitude of the force sensed by the drop hammer impact head, and the maximum displacement indicates the displacement change of the drop hammer impact head when the composite material is destroyed.

[0101] Table 2 Test results of dynamic mechanical performance indicators of the embodiment of the present invention and comparative example 1

[0102]

[0103] The results in Table 2 show the peak force magnitude and maximum displacement of Embodiments 1-5 and Comparative Example 1 under four energy impacts (10J, 30J, 50J and 70J). Embodiments 1-5 of the present invention all exhibit excellent energy absorption and shock absorption and toughening effects under different energy impact conditions, and have enhanced cushioning effect and structural integrity.

[0104] According to Table 2, Figure 3 and Figure 4 The results show that, compared with embodiments 1-5, especially compared with embodiments 2-5, comparative example 1 has a larger peak force and a smaller maximum displacement under different energy impacts. For example, under 10J energy impact, the peak force of Example 5 decreased by 33.6% and the maximum displacement increased by 53.9% compared with comparative example 1. This shows that comparative example 1 has lower toughness and only has a smaller buffering effect on impact force, which shows that the composite material is relatively brittle. This shows that the composite material of the present invention has better toughness and buffering effect.

[0105] Comparing the results of implementation schemes 1-5, it can be seen that as the content of toughening agent in the basalt fiber reinforced composite material increases, the peak force of the composite material gradually decreases and the maximum displacement gradually increases. This may be related to the influence of the toughening agent on the internal structure and performance of the composite material. For example, the addition of the toughening agent can absorb part of the impact energy of the punch, and the load transmitted to the drop hammer punch becomes smaller, which reduces the peak force. The addition of the toughening agent can also greatly improve the toughness of the composite material. Under 10J energy impact, the maximum displacement of implementation scheme 5 is increased by 53.9% compared with that of comparative example 1; under 70J energy impact, the maximum displacement of implementation scheme 5 is increased by 58.6% compared with that of comparative example 1. It can be seen that compared with 10J energy impact, the maximum displacement of the composite material of the present invention under 70J energy impact is still greatly improved compared with comparative example 1, and the increase is even higher than the value under 10J energy impact conditions. This shows that the composite material of the present invention can still maintain better toughness under high stress.

[0106] Example 3 Toughening effect of the toughening agent of the present invention on the resin matrix

[0107] According to the method of step 1 and step 2 in Example 1, a mixed liquid of the modified resin matrix was prepared according to the mass ratio of the following Table 3, wherein the vacuum degassing treatment included pouring the mixed liquid into a cylindrical silicone mold (aspect ratio 0.5, diameter 72 mm, length 36 mm), and degassing in a vacuum drying oven to remove bubbles generated during the stirring process.

[0108] Table 3 toughening agent reinforced resin matrix dosage table

[0109]

[0110] The obtained mixed liquid of the modified resin matrix is ​​cured, including curing at a suitable temperature (25°C) and time (more than 12 hours). After the curing is completed, the toughening agent-reinforced resin matrices STU0, STU1, STU2 and STU3 are obtained, corresponding to the toughening agent dosage of 0%, 10%, 20% and 30%, respectively. The error of the obtained toughening agent-reinforced resin matrix model is within 0.1mm. The shrinkage of the matrix material after curing may cause the surface to be uneven. A grinder and sandpaper can be used for grinding to ensure that the flatness meets the specifications.

[0111] The toughening agent-reinforced resin matrix prepared above was subjected to Hopkinson pressure bar tests at impact pressures of 0.2 MPa, 0.3 MPa and 0.4 MPa, respectively. The experimental results are as follows: Figure 5 The schematic diagram of the device used in this experiment is shown in Figure 6 shown.

[0112] Under 0.4Mpa impact air pressure, after STU0-3 was impact loaded by Hopkinson bar, the shape was as follows Figure 7 As shown. Under 0.4MPa impact pressure, the pure STU0 resin matrix is ​​brittle and has poor impact resistance, so it suffers brittle failure under impact load. However, with the increase of toughening agent dosage, the impact resistance of toughened resin matrix is ​​significantly improved; especially when the toughening agent dosage reaches 30%, the STU3 toughened resin matrix is ​​not even damaged, which shows that the toughening agent dosage has a significant improvement on the toughness of the resin.

[0113] according to Figure 5 The results show that under 0.2MPa impact pressure, when the toughening agent content reaches 30% (STU3), the peak stress decreases by 51.5% and the peak strain increases by 44.5% compared with pure resin (STU0); under 0.3MPa impact pressure, when the toughening agent content reaches 30% (STU3), the peak stress decreases by 64.8% and the peak strain increases by 36.5% compared with pure resin (STU0); under 0.4MPa impact pressure, when the toughening agent content reaches 30% (STU3), the peak stress decreases by 72.6% and the peak strain increases by 26.5% compared with pure resin (STU0). It can be seen that under high strain, the shear thickening of the toughening agent plays an energy absorption and shock reduction role, resulting in a smaller peak stress for the resin matrix reinforced by the toughening agent, while the toughening effect of the nanoparticles of the toughening agent leads to a larger strain range.

[0114] In summary, the basalt fiber reinforced composite material with better toughness and its preparation method proposed in the present invention have significant advantages and innovations, can meet the needs of different fields for high-performance composite materials, and provide new ideas and solutions for the development and application of the field of materials engineering.

[0115] The embodiments of the present invention are described in detail above, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. The true scope and spirit of the present invention are shown by the attached claims, and the description and embodiments are only exemplary.

Claims

1. A method for preparing a basalt fiber reinforced composite material, characterized in that: It includes the following steps: Preparation of toughening agent: mixing nano silicon dioxide powder with polyethylene glycol to obtain toughening agent; Preparation of modified resin matrix: mixing the toughening agent with the resin matrix, the first surfactant and the curing agent to obtain the modified resin matrix, wherein the mixing includes mechanical stirring, ultrasonic treatment and low temperature heating technology; Preparation of modified basalt fiber: providing cut basalt fiber cloth and bonding the cross sections, mixing the toughening agent with the second surfactant, impregnating the basalt fiber cloth, compacting the basalt fiber cloth, and curing by heat treatment to obtain modified basalt fiber; Curing and molding of composite materials: the modified resin matrix and the modified basalt fiber are made into composite materials through vacuum bag pressure infusion molding process.

2. The method according to claim 1, characterized in that The bonding section includes thermal compression bonding, in which the basalt fiber cloth sections are heated and pressed together under certain temperature and pressure conditions, so that the sections are bonded through melting and solidification of thermoplastic materials.

3. The method according to claim 2, characterized in that The thermoplastic material is selected from one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polycarbonate, polyamide, polyoxymethylene, and polymethyl methacrylate.

4. The method according to claim 3, characterized in that The temperature is 150°C; The pressure is 5Mpa; The thermoplastic material is polyethylene.

5. The method according to claim 1, characterized in that The compaction includes putting the basalt fiber cloth into a roller press and rolling a roller thereon to roll the basalt fiber cloth; wherein the rolling speed of the roller is 1.5 m / min and the size of the roller is 150×250 mm.

6. The method according to claim 1, characterized in that The end point of impregnating and compacting the basalt fiber cloth is that the difference in mass between the basalt fiber cloth after impregnation and before impregnation does not exceed 1%.

7. The method according to claim 1, characterized in that In the preparation of the modified basalt fiber, the heat treatment curing includes placing the impregnated basalt fiber in an oven at 120° C. for curing for more than 6 hours to obtain the modified basalt fiber.

8. The method according to claim 1, characterized in that The modified basalt fiber has a unit area mass of 350 g / m 2 The tensile strength in the warp direction is 3263N / 5cm, the tensile strength in the weft direction is 2208N / 5cm, and the elongation at break is 3%.

9. The method according to claim 1, characterized in that: The nano silicon dioxide powder is in the form of one or more of sphere, rod, fiber and porous.

10. The method according to claim 1, characterized in that The particle size of the nano silicon dioxide powder ranges from 12nm to 200nm.

11. The method according to claim 1, characterized in that: The polyethylene glycol is selected from one or more of polyethylene glycol 200, polyethylene glycol 400 and polyethylene glycol 600.

12. The method according to claim 1, characterized in that The resin matrix is ​​selected from epoxy acrylic resin, polyester resin or unsaturated polyester resin.

13. The method according to claim 1, characterized in that The first surfactant is selected from one or more of sodium dodecyl sulfate (SDS), quaternary ammonium salts, and polysorbate 80; The second surfactant is one or more of alkyl dimethyl betaine, sulfoethyl betaine, and phosphate betaine.

14. The method according to claim 1, characterized in that The curing agent includes one or more of methyl ethyl ketone oxide, cumene hydroperoxide and dodecyl peroxide.

15. A basalt fiber reinforced composite material, characterized in that: It is prepared by the method according to any one of claims 1-14.

16. Use of the composite material according to claim 15 in the fields of construction, automobile and military industry.

17. The use according to claim 16, wherein the composite material is used for bridge floors, automobile body parts and bulletproof structures.

Citation Information

Patent Citations

  • Fiber-reinforced resin-based composite material based on shear thickening fluid and preparation method of fiber-reinforced resin-based composite material

    CN118599288A

Cited By

  • A high barrier tear resistant polyethylene film material and its preparation method and use

    CN122706006A